Vector Control Realization of DFIG Under Grid Abnormalities using Real Time Digital Simulator - Kanungo Barada Mohanty; Satish Choudhury; Madhu Singh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
A grid connected doubly-fed induction generator (DFIG) system, driven by variable speed wind turbine is considered in this research to satisfy grid code requirements. Remaining grid synchronized and stable under voltage sag and voltage swell, obtaining power control through dc link voltage control, and providing unity power factor at grid terminals are the achievements. The DFIG system uses two back-to-back converters. Vector control strategy is used with the grid side and rotor side converters, and taken up for research for further improvement. The grid side converter controls dc-link voltage and maintains unity power factor at the grid connection point. The rotor side converter supplies the reactive power of the machine and maintains the speed constant irrespective of the transient behavior of the grid. In this paper the behavior of the DFIG system is analyzed under grid voltage fluctuation and the experimental results are obtained using RT-LAB. Main contribution of this work is in improving the DFIG system performance with grid low voltage and over voltage ride through capability through simulation, and its real time experimental verification.